Revitalisasi Simbolik Istana Alwatzikhoebillah Sambas Pasca-Kolonial: Pelestarian Warisan Budaya Melayu dalam Perspektif Sejarah Material (2025) - Posha, Beti Yanuri; Azani, Deki; Anisa, Nur (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The Symbolic Revitalization of the Alwatzikhoebillah Palace in Post-Colonial Sambas: Preserving Malay Cultural Heritage from a Material History Perspective (2025) examines how the Alwatzikhoebillah Palace was managed and preserved as a form of cultural heritage representing the center of power of the Sambas Sultanate and a symbol of Malay cultural identity. This research uses historical methods with a qualitative approach, through heuristics, verification, interpretation, and historiography. Data collected from palace archives, colonial documents, old photographs, government records, and interviews with prominent figures and the families of the heirs were then analyzed to understand the palace's physical condition, social function, and symbolic meaning as of 2025. The results indicate that several parts of the building, such as the roof, ceiling, and foundation, have deteriorated, necessitating preservation efforts. Conservation efforts include the rehabilitation of building materials, regulation-based conservation, and the preservation of the palace's original form, through collaboration between the government and the community. These efforts not only prevent the loss of historical and cultural value but also strengthen local identity and provide a means of historical education for future generations.